Factors influencing the adoption of Integrated Pest Management (IPM) techniques by the FSTP-trained farmers in Balamban, Cebu - Yap, Cheddie Legaspi (University of the Philippines in the Visayas-Cebu College, 2007)
Pesticide application has detrimental impacts on health and the environment. Meanwhile, integrated pest management (IPM) avoids pesticide application, and the hazardous effect of pesticides. IPM has economic, health and ecological/environmental benefits. Understanding the factors that influence the level of IPM adoption is essential to the effective implementation of IPM programs and projects as well as the promotion of sustainable agriculture in the country. This study aims to determine the factors influencing the adoption of IPM among FSTP-trained framers in Balamban, Cebu. The study hypothesized that gender, age, educational attainment, income, livelihood, farming experience, farm ownership, crops planted, IPM knowledge, and perception on the technicaal requirements of IPM, IPM's economic, health, and environemental benefits, and impact of crop protection activities in the adjacent farms are factors that influence the adoption of IPM. Data wer gathered through the conduct of survey and interview with key informants.Results showed positive correlation between level of IPM adoption and perception on the technical requirements of IPM (r=0.515, p<0.05) as well as between level of IPM adoption and perception on IPM's environmental benefits (r+o.471. p<0.05). This means that positive or favorable perceptions on the technical requirements of PM and environmental benefits of IPM could lead to adoption of the integrated pest management techniques.